Estimation of the willingness to pay in two aquifers in Baja California, Mexico - Elizondo, Lázaro S.; Aguilar-Ibarra, Alonso; Manson, Robert H.; Mendoza-Espinosa, Leopoldo G. (Tecnología y ciencias del agua, 2025)
This study presents an assessment of the perceptions and willingness-to-pay (WTP) of farmers using groundwater for irrigation in two aquifers in northern Baja California, Mexico. Contingent Valuation (CV) measured their WTP to ensure availability of groundwater in the future. Data from surveys of 70 and 54 farmers in the Maneadero and Guadalupe valleys, respectively, were combined and analyzed using logistic regression. Farmer WTP is influenced by variables reflecting "present water scarcity for agricultural use", "education and family income levels", "partial use of wastewater for irrigation", "water quality", and "payment amount". A WTP estimate of $US 0.13/m3 suggests that the environmental cost of depleting aquifers over a 20-year span could reach $US 17.4-24.9 million for the Guadalupe aquifer and $US 20.50 million for the Maneadero aquifer. This information could serve as a starting point to help decision makers in northern Mexico design more environmentally sustainable pricing policies, including investing revenues in long-term aquifer restoration.